2023
DOI: 10.1177/0271678x231167753
|View full text |Cite
|
Sign up to set email alerts
|

Sex modifies the relationship between age and neurovascular coupling in healthy adults

Abstract: Neurovascular coupling (NVC) is the matching between local neuronal activity and regional cerebral blood flow (CBF), but little is known about the effects of age and sex on NVC. This study aimed to investigate the relationships and interaction between age and sex on NVC. Sixty-four healthy adults (18–85 years, N = 34 female) completed a visual stimulus evoked NVC assessment to a flashing checkerboard. NVC responses were measured in the posterior cerebral artery (PCAv) using transcranial Doppler ultrasound. A h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 81 publications
0
4
2
Order By: Relevance
“…Second, the gender dimorphism of this study may have been overlooked in this study. A growing body of research has highlighted that women's vascular regulatory capacity diminishes with age, and women tend to have a poorer prognosis for stroke compared to men 52–55 . While our study did not reveal distinct gender differences between the ISR and NR groups, the potential impact of sex dimorphism on outcomes cannot be discounted.…”
Section: Discussioncontrasting
confidence: 80%
“…Second, the gender dimorphism of this study may have been overlooked in this study. A growing body of research has highlighted that women's vascular regulatory capacity diminishes with age, and women tend to have a poorer prognosis for stroke compared to men 52–55 . While our study did not reveal distinct gender differences between the ISR and NR groups, the potential impact of sex dimorphism on outcomes cannot be discounted.…”
Section: Discussioncontrasting
confidence: 80%
“…Previous studies demonstrated that sexual dimorphism has been increasingly recognized in healthy population and patients as an important factors that might modify the response to therapies in neurovascular disorders. 19 , 20 , 21 However, the influence from sexual dimorphism was not found in the current study. On one hand, the result may be partially attributed to relatively unbalanced sample size between male and female patients in the analysis.…”
Section: Discussioncontrasting
confidence: 75%
“…Other studies showed that the effect of sexual dimorphism about age on the matching between local neuronal activity and regional cerebral blood flow only apparent in females but not males, it may be related to the loss of estrogen in postmenopausal women, which could lead to a greater decline in cerebral blood flow. 32,33 Similarly, others have found that patients with high BMI and diabetes have increased postoperative complications, 34 and that the risk of stroke was higher with vascular and neurosurgical operations. 28 Interestingly, the association of BMI > 22.64 kg/m 2 with perioperative ischemic stroke was also evident in the neurosurgical subgroup, calling for increased attention to patients in this subgroup that must undergo neurosurgery.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study showed that female is associated with more than a threefold increased risk of perioperative stroke, 31 which may be related to the slower metabolism of female patients with increased BMI having, which is more likely to cause abnormal blood lipid metabolism, resulting in the weakening of the automatic regulation of cerebral blood flow. Other studies showed that the effect of sexual dimorphism about age on the matching between local neuronal activity and regional cerebral blood flow only apparent in females but not males, it may be related to the loss of estrogen in postmenopausal women, which could lead to a greater decline in cerebral blood flow 32,33 . Similarly, others have found that patients with high BMI and diabetes have increased postoperative complications, 34 and that the risk of stroke was higher with vascular and neurosurgical operations 28 .…”
Section: Discussionmentioning
confidence: 99%